The Influence of Education Expenditure, Health Expenditure, and the Gini Ratio on Human Development - Aulia, Tri Setya; Devanto Shasta Pratomo (Journal of Development Economic and Social Studies, 2025)
Regional development can be assessed by the extent of human development within the area. High-quality human resources are expected to contribute positively to increased productivity. In this regard, the commitment of local governments to promoting human development is crucial, particulary through the allocation of public expenditure to key sectors. This study investigates the impact of education expenditure sourced from the Early Childhood Education Operational Assistance (BOP PAUD), health expenditure sourced from the health Operational Assistance (BOK), and income inequality as measured by the gini ratio on the Human Development in the Special Region of Yogyakarta (DIY). The analysis is based on secondary data from five districts and municipalities within the province. A quantitive approach using panel data regression is employed. The results show that education expenditure sourced from BOP PAUD has a statistically significant negative effect on HDI, health expenditure sourced from BOK has a statistically significant positive effect, while the gini ratio has no significant effect on HDI.